2016
DOI: 10.1177/0960327116652460
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomic analysis of the protective effect of quercetin on the toxicity induced by mixture of organophosphate pesticides in rat urine

Abstract: The present study aims to investigate the protective effect of quercetin against the joint toxic action induced by the mixture of four organophosphate pesticides (mixture-OPs) (dimethoate, acephate, dichlorvos, and phorate) at their corresponding no observed adverse effect level (NOAEL) using metabonomics. Rats were randomly divided into control, quercetin-treated, mixture-OPs-treated, and quercetin plus mixture-OPs-treated groups. Mixture-OPs and quercetin were given to the rats daily through drinkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Specifically, with the development of industrial technology and the progress of science and technology, the damage of chemical raw materials to the kidney has grown immensely prominent. Data from animal models have shown that the protective effect of quercetin is closely related to the clearance of free radicals and reduction of lipid peroxidation in both industrial chemical raw materials and heavy metal and diesel particulate pollution (Li et al, 2016b;Qi et al, 2017;Uthra et al, 2017;Alshanwani et al, 2020;Morsi et al, 2022). Moreover, Quercetin was also found to reduce organophosphorus pesticide mixture-induced nephrotoxicity by regulating fatty acid, energy and sex hormone metabolism, protecting antioxidant defense systems and reducing DNA damage (Qi et al, 2017).…”
Section: Quercetin In Traditional Herbal Medicinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, with the development of industrial technology and the progress of science and technology, the damage of chemical raw materials to the kidney has grown immensely prominent. Data from animal models have shown that the protective effect of quercetin is closely related to the clearance of free radicals and reduction of lipid peroxidation in both industrial chemical raw materials and heavy metal and diesel particulate pollution (Li et al, 2016b;Qi et al, 2017;Uthra et al, 2017;Alshanwani et al, 2020;Morsi et al, 2022). Moreover, Quercetin was also found to reduce organophosphorus pesticide mixture-induced nephrotoxicity by regulating fatty acid, energy and sex hormone metabolism, protecting antioxidant defense systems and reducing DNA damage (Qi et al, 2017).…”
Section: Quercetin In Traditional Herbal Medicinesmentioning
confidence: 99%
“…Data from animal models have shown that the protective effect of quercetin is closely related to the clearance of free radicals and reduction of lipid peroxidation in both industrial chemical raw materials and heavy metal and diesel particulate pollution (Li et al, 2016b;Qi et al, 2017;Uthra et al, 2017;Alshanwani et al, 2020;Morsi et al, 2022). Moreover, Quercetin was also found to reduce organophosphorus pesticide mixture-induced nephrotoxicity by regulating fatty acid, energy and sex hormone metabolism, protecting antioxidant defense systems and reducing DNA damage (Qi et al, 2017). Quercetin may regulate the metabolism of phospholipids, energy, fatty acids and amino acids to protect the kidney against acrylamide-induced nephrotoxicity (Bao et al, 2017; Frontiers in Pharmacology frontiersin.org Bo et al, 2018).…”
Section: Quercetin In Traditional Herbal Medicinesmentioning
confidence: 99%
“…[ 44 ] Also, dimethylphosphate, dimethyldithiophosphate, and diethylphosphate can be detected in patients or workers who are exposed to a mixture of OPs chemicals. [ 73 ] And urinary trichloro‐2‐pyridinol (TCPy) is often used as early indicator of exposure to Chlorpyrifos, whereas blood ChE activity decreases after severe clinical manifestation is observed. [ 49 ] Furthermore, peptides and fragmented proteins have significant role in analytical biomedicine.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that quercetin has anti-oxidation, anti-inflammatory, anti-cancer, antiaggregatory and immunomodulatory effects. 4 Epidemiological studies have suggested that quercetin may reduce the risk of hypercholesterolemia, atherosclerosis and other chronic diseases. 5,6 Some studies have also indicated that quercetin can alleviate Cd-induced kidney, testicular and nerve damage via inhibition of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%